Fabrication of calcium phosphate coating on pure magnesium substrate via simple chemical conversion coating: surface properties and corrosion performance evaluations - Mohd Amin, Farhan Zaludin (Elsevier, 2020)
Link to publisher's homepage at https://www.sciencedirect.com/